Modeling and Data testing for Indian Universities Clusters (International Journal of Engineering and Computer Science, 2013)
This paper gives Modeling and Data testing on Indian Universities Clustering with respect to Statistical and Mathematical methods. In next phase of action we can implement with different Data mining tools for observe the difference between them. Using different modeling techniques we can easily find out the outliers in the data. In this paper we discussed only on numeric data very purely and not allowed any other type of data. Authors in this paper consider the two types of data set one is given set and another is 50% random set from given data. Authors already published about the data preparation in their published paper [51], pp 31-32.